Impact of Digital Literacy Skills on Undergraduate Performance in Nigeria (AFRICAN JOURNAL OF APPLIED RESEARCH, 2025)
Purpose: The broad purpose of this study is to investigate the digital literacy skills of undergraduate Students Performing via Online Tests in Lagos State, Nigeria. The objective is to examine how online tests affect undergraduates' critical thinking skills and ability to analyse information.Design/Methodology/Approach: The descriptive research design was adopted. Second-year undergraduate students were used as the population. They were those who used computers in school-based tests and examinations. Two testing instruments, aw score from the Entrepreneurship Computer-Based Test and a structured instrument QDLSCUPOT (a 4-Likert scale type of closed-ended format), were used in data generation. A multi-stage sampling process of 21 departments using a simple random sampling technique was used to select 420 participants for this work. Using a Statistical Package, data were analysed using Pearson product-moment correlation at a 0.05 significant level.Research Limitation: The study is confined to a specific group of undergraduate students in Lagos State, which may limit the generalizability of the findings to other regions or institutions within Nigeria or beyond.Findings: Findings show that digital literacy plays a significant and positive role in the outcome of undergraduate performance. The study concludes that the technology is less expensive, has less manpower demand, has lower anxiety levels, is stress-free in marking and scoring, and develops undergraduates' psychomotor and cognitive skills.Practical Implication: Developing critical thinking skills and the ability to analyse information accurately is a function of digital literacy efficiency and should be encouraged.Social Implications: The disparity in digital literacy skills can entrench existing social inequalities, marginalising students from disadvantaged backgrounds and affecting their long-term socio-economic mobility.Originality and Value: This study contributed to the pool of knowledge on promoting critical thinking skills and promoting learners' analytical mindsets.
Keywords: Digital. online test. performance. score. undergraduate